2021
DOI: 10.1038/s41467-021-22335-5
|View full text |Cite
|
Sign up to set email alerts
|

Primate ventral striatum maintains neural representations of the value of previously rewarded objects for habitual seeking

Abstract: The ventral striatum (VS) is considered a key region that flexibly updates recent changes in reward values for habit learning. However, this update process may not serve to maintain learned habitual behaviors, which are insensitive to value changes. Here, using fMRI in humans and single-unit electrophysiology in macaque monkeys we report another role of the primate VS: that the value memory subserving habitual seeking is stably maintained in the VS. Days after object-value associative learning, human and monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Like the amygdala, the VS often shows anticipatory activity patterns that correlate with goal values (Bartra et al, 2013; Haber & Knutson, 2010). However, growing evidence suggests that the VS may inherit these goal-value signals from the amygdala and use them to stabilize choices over time (Averbeck & Costa, 2017; Kang et al, 2021). Reward-predictive activity in the amygdala precedes that in the VS and when the amygdala is damaged or inhibited via optogenetic stimulation it disrupts the contribution of the VS to goal-directed behavior (Ambroggi et al, 2008; Stuber et al, 2011).…”
Section: Interactions Between the Amygdala And Pfcmentioning
confidence: 99%
“…Like the amygdala, the VS often shows anticipatory activity patterns that correlate with goal values (Bartra et al, 2013; Haber & Knutson, 2010). However, growing evidence suggests that the VS may inherit these goal-value signals from the amygdala and use them to stabilize choices over time (Averbeck & Costa, 2017; Kang et al, 2021). Reward-predictive activity in the amygdala precedes that in the VS and when the amygdala is damaged or inhibited via optogenetic stimulation it disrupts the contribution of the VS to goal-directed behavior (Ambroggi et al, 2008; Stuber et al, 2011).…”
Section: Interactions Between the Amygdala And Pfcmentioning
confidence: 99%
“…That both lesions and optogenetic activation of DLS could similarly impair reward sensitivity may seem paradoxical, but it is possible that overactivation of DLS in the current study effectively renders mice outcomeinsensitive by driving overreliance on previously learned action valuation. The striatum is thought to encode both object and action-outcome valuation across both dorsal and ventral aspects (Yamada et al, 2013;Kang et al, 2021;Guo et al, 2018;Kim et al, 2015;Yasuda et al, 2012); however, activity in dorsal striatum preferentially encodes valuation of specific actions (Burton et al, 2015;Nakamura et al, 2012;Hollerman et al, 1998), while ventral striatum better tracks outcomes. Studies in primates have also noted long-term value storage in brain centers promoting inflexible responding, including the posterior/tail of the striatum (Kim et al, 2015;Griggs et al, 2017;Guo et al, 2018) and SNr (Yasuda et al, 2012).…”
Section: Optogenetic Self-stimulation Of Distinct Striatal Subregions Alters Behavioral Strategiesmentioning
confidence: 99%
“…Nowadays, much attention is being paid to the welfare of laboratory animals (Reeb-Whitaker et al, 2001 ; Gonder and Laber, 2007 ), and the conditions of keeping laboratory animals have been the focus of several studies, as environmental factors such as cage size may interfere with the results of behavioral tests (Loo et al, 2001 ; Mcglone et al, 2001 ; Wolfer et al, 2004 ; Julia et al, 2008 ). For example, previous studies have shown significant effects of cage size on reproductive performance (Julia et al, 2008 ; Whitaker et al, 2009 ), aggressiveness level (Loo et al, 2001 ), anxiety level (Bellei et al, 2011 ), and exploration and cognitive abilities (Forsyth and Young, 2007 ; Julia et al, 2008 ; Line et al, 2010 ). Therefore, animal welfare, including cage size, is critical to the reliability of research using laboratory animals.…”
Section: Introductionmentioning
confidence: 99%